Synthesis of the Switched Bias Proportional Navigation Guidance Law to Destroy Complexly Maneuvering Targets - Tien Trung, Dang; Van Bang, Nguyen (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This paper presents the results of synthesis of guidance law for homing missile to destroy highly and complexly maneuvering targets. The aim is to realize the guidance methods applied to modern homing missiles. The algorithm is simple, highly convergent, stable and has small errors. The efficiency of the algorithm is verified through simulation, the results are reliable. New guidance law for short range flight missiles, based on the theory of variable mode structure. The new guidance law is built around the basic the proportional navigation guidance law with a switched bias added to the guidance law to bring the line of sight angle towards zero, even when the target is maneuvering.